Seçim Sosyolojisi ve Lübnan'da Seçimler - Bozbaş, Gökhan; Rawi, Badria (Muş Alparslan Üniversitesi, 2020)
In Lebanon, in 2018, after a 9-year break, the elections were held for the first time. The elections, far from putting an end to debates, it made debates deepen. However, the debates for Lebanon, may turn into a way out and an upper identity building process. Lebanon, for more than a century, has a social structure where individuals define themselves through their sects. Lebanon, not only had sectarian fight problems inside but also had an open structure to outside interventions. Although recent developments in Lebanon are promising developments for the construction of upper identity within the country, the wrong choices of decision-makers can push them into deeper conflicts. Yet, in recent years, Lebanon has been a political area, where some political actors have faced sectarian preferences.

Lübnan’da 2018 yılında 9 yıllık bir aranın ardından ilk defa seçimler yapıldı. Seçimler Lübnan’da tartışmaları bitirmemiş bilakis daha da derinleştirmiştir. Fakat bu derinleşen tartışmalar Lübnan için bir çıkış, bir üst kimlik inşa sürecine dönüşebilir. Lübnan bir asrı aşkın bir süredir bireylerin kendilerini mezhepleri üzerinden tanımladıkları bir sosyal yapıya sahiptir. Lübnan mezhepçilik kavgasından sadece içeride sorunlar yaşamamıştır. Aynı zamanda dışarıdan müdahalelere de sosyal olarak her daim açık bir yapı sunmuştur. Lübnan’da son dönemlerde ortaya çıkan yeni gelişmeler ülke içerisinde üst kimliğin inşası adına umut verici gelişmeler olmakla beraber karar alıcıların yanlış tercihleri onları daha derin çatışmaların içine itebilir. Zira Lübnan son yıllarda özellikle bazı siyasi aktörlerin mezhep üstü tercihlerle karşılaştığı bir siyasi alan olmuştur.
The Sociology of Election and Elections in Lebanon
anemon
Keywords: Election sociology; Lebanon; Sectarianism; Voter behavior; Seçim sosyolojisi; Lübnan; Mezhepçilik; Seçmen davranışları